Experimental and Theoretical Study on the Biomolecular Interaction of Novel Acenaphtho Quinoxaline and Dipyridophenazine Analogues. Issue 38 (10th October 2018) - De, Sourav; Sarkar, Bidisha; Jadhav, Gajanan Raosaheb; Ramasamy, Selva Kumar; Banerjee, Subhasis; Moorthy, Anbalagan; Paira, Priyankar; K, Ashok Kumar S
Abstract: In this report, two different types of quinoxaline derivatives have been developed with an idea that these molecules are composed of planar structure with extensive π‐delocalization. Accordingly, compounds such as 9‐bromoacenaphtho [1, 2‐ b ]quinoxaline (3 ), 4‐(acenaphtho [1, 2‐ b ] quinoxalin‐9‐yl) benzaldehyde (5 ), 11‐bromodipyrido [3, 2‐ a :2′, 3′‐ c ] phenazine (3′ ) and 4‐(dipyrido [3, 2‐ a :2′, 3′‐ c ] phenazin‐11‐yl) benzaldehyde (5′ ) were prepared by a sonication method. In order to prove these compounds as potential anticancer agents, binding studies with calf thymus deoxyribonucleic acid (CT‐DNA) and bovine serum albumin (BSA) have been established by absorption and fluorescence studies. The DNA interaction with prepared compounds shows that quinoxaline (3 and5 ) and phenazine derivatives (3′ and5′ ) are bind to DNA through intercalation and electrostatic modes. The binding strength of3′ and5′ with DNA found to be stronger than other two derivatives (3 and5 ). The magnitude of5 and5′ exhibits 10‐fold more binding efficacy with protein BSA than compound3′ but compound3 did not show any binding efficacy with BSA. The MTT (3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) analysis reveals that5′ exhibits highly selective cytotoxicity profile in HeLa cell line and moderate cytoselectivity in human epithelial colorectal adenocarcinoma cells (Caco‐2) cell line with respect to the normal cell line. However, compound3 showed best potency and selectivity in Caco‐2 cells. Abstract : Novel Acenaphtho quinoxaline and Dipyridophenazine analogues were synthesized using a simple and efficient procedure. Biomolecular interaction was carried out by absorption and fluorescence studies. These results suggest that the quinoxaline derivatives bind to DNA through intercalation and electrostatic mode. The significant hypochromism in fluorescence observed from BSA binding study indicates the strong binding of these compounds with BSA which helps in transport of the compounds in biological systems. These compounds are also exhibited high potency and selectivity in cancer cells than normal cells.